PENGARUH KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SMP - Sucipno Sucipno; Rambat Nur Sasongko; Zakaria Zakaria (Manajer Pendididikan, 2017)
The general purpose of this research was to analyze the effect of principal instructional leadership and job satifaction toward teacher job performance at Junior High School in Ulok Kupai District Bengkulu Utara Regency. The method of the research used survey. The result showed (1) the principal instructional leadership gave effect which significance toward teacher job performance at Junior High School in Ulok Kupai District Bengkulu Utara Regency.  (2) the job satisfaction gave sinificance effect toward teacher job performance at Junior High School in Ulok Kupai District Bengkulu Utara Regency (3) the principal instructional leadership and job satisfaction gave significance effect toward teacher job performance at Junior High School in Ulok Kupai District Bengkulu Utara Regency.